Hambatan Implementasi Asean Convention Against Trafficking in Persons, Especially Women and Children di Provinsi Sulawesi Selatan - Tempali, Dewi Kartika; Burhan, Zulkhair (Journal of International and Local Studies, 2025)
This writing was written to find out what obstacles were experienced in the process of implementing the Asean Convention Against Trafficking in Persons, Especially Women and Children (ACTIP) in South Sulawesi Province so that it had not optimally achieved its goal of preventing and handling human trafficking cases. This research was conducted qualitatively, using a descriptive approach. The concept used as a framework for thinking in answering the problem formulation is Cornelius Friesendorf's counter-trafficking concept. Several data collection techniques used are; interviews and literature review through various literature sources. The results of the research obtained by the author show that there are several obstacles to implementing ACTIP in South Sulawesi. Obstacles experienced include ACTIP's inconsistency with existing legal norms in Indonesia, the absence of consistent victim identification guidelines in ACTIP, and the lack of state resources and capacity.